Findings Predictive of Poor Outcome in Grade 5 Subarachnoid Hemorrhage: A Cohort Study. (21st November 2021) - Kramer, Andreas H.; Couillard, Philippe L.; Kromm, Julie A.; Ruddell, Stacy; Demers-Marcil, Simon; Mitha, Alim P.; Sutherland, Garnette R.; Wong, John H.
ABSTRACT: Background: Most patients with World Federation of Neurological Surgeons (WFNS) grade 5 subarachnoid hemorrhage (SAH) have poor outcomes. Accurate assessment of prognosis is important for treatment decisions and conversations with families regarding goals of care. Unjustified pessimism may lead to "self-fulfilling prophecy, " where withdrawal of life-sustaining measures (WLSM) is invariably followed by death. Methods: We performed a cohort study involving consecutive patients with WFNS grade 5 SAH to identify variables with >= 90% and >= 95% positive predictive value (PPV) for poor outcome (1-year modified Rankin Score >= 4), as well as findings predictive of WLSM. Results: Of 140 patients, 38 (27%) had favorable outcomes. Predictors with >= 95% PPV for poor outcome included unconfounded 72-hour Glasgow Coma Scale motor score <= 4, absence of >= 1 pupillary light reflex (PLR) at 24 hours, and intraventricular hemorrhage (IVH) score of >= 20 (volume >= 54.6 ml). Intracerebral hemorrhage (ICH) volume >= 53 ml had PPV of 92%. Variables associated with WLSM decisions included a poor motor score (p < 0.0001) and radiographic evidence of infarction (p = 0.02). Conclusions: We identified several early predictors with high PPV for poor outcome. Of these, lack of improvement in motor score during the initial 72 hours had the greatest potential for confounding from "self-fulfilling prophecy." Absence of PLR at 24 hours, IVH score >= 20, and ICH volume >= 53 ml predicted poor outcome without a statistically significant effect on WLSM decisions. More research is needed to validate prognostic variables in grade 5 SAH, especially among patients who do not undergo WLSM.